2017
DOI: 10.1111/jce.13248
|View full text |Cite
|
Sign up to set email alerts
|

Eleven‐year trends of inpatient pacemaker implantation in patients diagnosed with sick sinus syndrome

Abstract: Background Pacemakers (PM) are used for managing sick sinus syndrome (SSS). This study evaluates predictors and trends of PM implantation for SSS. Methods Patients were identified from the National Inpatient Sample dataset (2003–2013). Included patients were ≥18 years old, had a diagnosis of sinus node dysfunction and atrial arrhythmia (i.e., SSS). Patients who died, transferred out, who had prior device, or had a defibrillator or resynchronization therapy device implanted were excluded. Included patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Narasimhan et al (2017) found that patients who were older and had hypertensive and syncopal symptoms had a higher probability of having PPM implantation compared to others. In addition to clinical variables, nonclinical variables such as socioeconomic status or gender may also influence the efficacy of PPMs in patients (Guha et al, 2017). Moreover, the patients’ biopsychosocial adjustment after PPM implantation plays an important role in determining their QoL.…”
Section: Background and Rationalementioning
confidence: 99%
“…Narasimhan et al (2017) found that patients who were older and had hypertensive and syncopal symptoms had a higher probability of having PPM implantation compared to others. In addition to clinical variables, nonclinical variables such as socioeconomic status or gender may also influence the efficacy of PPMs in patients (Guha et al, 2017). Moreover, the patients’ biopsychosocial adjustment after PPM implantation plays an important role in determining their QoL.…”
Section: Background and Rationalementioning
confidence: 99%
“…In patients age ≥ 80 years, women predominantly received single‐chamber ventricular devices, whereas men received more dual‐chamber devices. Guha et al analyzed 328 670 patients admitted for SSS (54.2% women) and found that women had lower rates of pacemaker implantation compared with men.…”
Section: Pacemakersmentioning
confidence: 99%
“…A recent U.S study investigated patients with sick sinus node syndrome and PPMs from 2003 to 2013. They found that income above median quartile had an increased risk of receiving an PPM [ 19 ], and one of their main explanations for this was patient affordability of PPM. The Danish healthcare which is available free of charge to all inhabitants independent of socioeconomic status should rule out any patient concerns about affordability.…”
Section: Discussionmentioning
confidence: 99%